INFÂNCIAS, RELAÇÕES ÉTNICO-RACIAIS E LITERATURA: DIÁLOGOS SINGULARES E PLURAIS A PARTIR DA OBRA “DA MINHA JANELA”, DE OTÁVIO JÚNIOR - Batista, Patrícia Barros Soares; Silva, Giane Maria da (Literatura em Debate, 2025)
To thematize children, their interactions, constructions, powers and experiences by making interlocution with the literary field opens space for the qualification of the debate on the representation of childhood, especially black infancy in literary works addressed to the child reader. In this sense, the present work aims to weave reflections on the tensions related to childhood, ethnic-racial relations and literature from the analysis of the book “Da minha janela”, by Otávio Júnior, awarded the Jabuti award for best work in the children’s category, in the year 2020. In contemporary production, the children’s literary book is a dialogue between text and reader and is expanded through the presence of different semioses through which multiple voices are heard, enhancing the senses. Methodologically we chose the analysis of the Bakhtinian discourse, in order to investigate the polyphony present in the text that invites us to look out the window and see the favela from the eyes of a black and peripheral child, taking the word and image as enunciative elements in the narrative construction. The results of this study reinforce the complexity and potential to thematize children, their interactions, constructions, powers and experiences by making interlocution with the literary field opens space for the qualification of the debate on the representation of childhood, especially black infancy in literary works addressed to the child reader. In this sense, the present work aims to weave reflections on the tensions related to childhood, ethnic-racial relations and literature from the analysis of the work "Da minha janela", by Otávio Júnior, awarded the Jabuti award for best work in the children’s category, in the year 2020. In contemporary production, the children’s literary book is a dialogue between text and reader and is expanded through the presence of different semioses through which multiple voices are heard, enhancing the senses. Methodologically we chose the analysis of the Bakhtinian discourse, in order to investigate the polyphony present in the text that invites us to look out the window and see the favela from the eyes of a black and peripheral child, taking the word and image as enunciative f illustrated books addressed to childhood and indicate that echoing historically muted voices is a way of resignifying the literary field. Thus, the conception of childhood is strengthened plural and vehement achievements in which children are understood in their singular ways of participating in the world, through constant processes of (re)elaboration of meanings and attribution of meanings on their perceptions, feelings and experiences, considering their ethnic-racial origins, class, among other aspects.